Specific language impairment : a look into auditory cortex in time window of 80-600ms post stimulus using magnetoencephalography - Keita, Pertti (2014)
Children with specific language impairment (SLI) have problems in expressing themselves verbally and are generally a few years behind other children in language skills. They have limited vocabulary and are often late to talk. We recorded auditory cortex’s response to speech sounds and non speech sound in SLI group and age matched control group using magnetoencephalography. Stimuli were presented as passive listening while children were watching TV and in active listening task. To account the different stages of auditory process we measured rather large time window of - 200 ms to 800 ms post stimulus. Active listening task evoked stronger response throughout the experiment. Where non speech sound (complex sound with 3 formants) induced the strongest activation for control group - this effect was not found in SLI group. Our results indicate some low level discrepancies how children with SLI process auditory stimuli.